SHAPING A NEW ETHICAL LANDSCAPE IN TEACHER EDUCATION: AN IRISH EXPERIENCE IN AN INTERNATIONAL CONTEXT - Dolan, Rose; Hogan, Pádraig (Bordón. Revista de Pedagogía, 2017)
INTRODUCTION. This article reviews a gradual but decisive transformation in teacher education in Ireland. It traces, firstly, the outlines of traditional models of teacher education — based historically on UK patterns. These rarely addressed directly the ethical dimensions of professional learning. Such learning largely consisted of acquaintance with a body of theory on the one hand, and on the other, initiation into inherited attitudes and practices for survival in the workplace. The article examines successive efforts to change these models. METHOD. Taking as an illustrative study the efforts of one university to transform this pattern, we explore how a new rationale emerged during the 1980s and progressively came to fruition thereafter. Critical attention is paid to concerns like the teacher’s ethical agency and reflective capacity. The research structure has five parts. The first sketches the historical context, revealing how key ethical questions often remained peripheral in teacher education. The second traces the different directions taken by teacher education in the UK and Ireland in the 1980s and provides a summary of the new rationale we developed at Maynooth. The third reviews the notion of teachers’ ethical agency, and its importance for that rationale. The fourth illustrates how the new rationale changed the experience of becoming a teacher, specifically through the Higher Diploma in Education. The final section reviews the consequences of the new approach and its broader import for national policy at a time when Ireland’s Teaching Council progressively embraced a critically reflective approach to teacher education as a whole. RESULTS. The results of the new approach are reviewed incrementally through the paper, to reveal how the ethical dimensions of professional learning became more central and more fruitful. DISCUSSION. The discussion, throughout the paper, focuses on the actions needed to make the ethical dimensions of professional learning more relevant and meaningful.